HEURISTIC LEARNING TECHNOLOGIES IN THE TRAINING OF TEACHERS - Yevdokimov, Victor (Continuing Professional Education: Theory and Practice, 2019)
The article contains the results of the scientific investigation of the problem of designing and functioning of heuristic learning technologies in the process of teacher training. The technology of heuristic learning is justified as a system of fundamental principles and concepts that define the objectives, tasks, content, system training organization, monitoring and evaluation of education results. Basic principles of heuristic learning: childhood centrist; productivity; subjectivity; self-knowledge, self-development and self-realization; causality; elective training (didactic choice); variability of training; pedagogical competence; professional analogies and borrowings; targeting clearly defined goals. The author outlines the meaning and defined methodological principles of designing and providing educational activities in conditions of heuristic learning in the preparation of future teachers. The analysis of technologies of heuristic learning aimed at the successful creation of an educational product - the leading goal of heuristic learning - and adequately assess the course and results of independent cognitive activity.